Physiological changes in glucose uptake by GLUT-4 in Gestational Diabetes Mellitus (Research, Society and Development, 2020)
This study aimed to identify the physiological changes that occur in the GLUT4 in glucose uptake in patients with gestational diabetes mellitus, which changes have resulted due to the increase of counterregulatory hormones insulin at physiological stress imposed by pregnancy and by predetermining factors that can be genetic and / or environmental factors, inflammatory mediators and insulin resistance. Given that all these metabolic changes interfere directly or indirectly in glucose uptake by GLUT-4, there was a literature review with descriptive, explanatory and qualitative approach about the changes suffered by this carrier in gestational diabetes mellitus. It is therefore concluded that metabolic changes suffered in DMG interfere directly in the expression and translocation of the GLUT-4 glucose transporter.